Revenue Administration : Developing a Taxpayer Compliance Program - Russell, Barrie (Technical Notes and Manuals; Technical Notes and Manuals, 2010)
This technical note describes the importance of a taxpayer compliance program. Improving tax compliance requires long-term reform efforts, beginning with strengthening the organization and management of the revenue agency, implementing robust collection systems, and building capacity in core tax administration functions. Reform of the legal framework and judiciary is also often required to ensure that the necessary powers, penalty regimes, and dispute resolution processes are in place. This note explains how countries can improve tax compliance. Steps in developing a taxpayer compliance program are also elaborated.